‘I know my rights, but am I better off?’: institutions and disability in Uganda - Owens, Trudy; Torrance, Samantha (Taylor & Francis, 2015)
Uganda is internationally recognised for both its legal and constitutional provisions for people with disabilities, and the presence of disabled persons’ organisations that provide informal advocacy and support. Using a unique dataset of 579 Ugandans with physical disabilities, we develop a conceptual framework on social capital to investigate the factors correlated with knowledge of formal institutions that target disability. In examining whether this knowledge results in higher incomes we find that gender matters. A woman’s education and membership of external networks are correlates of knowledge; higher levels of this knowledge are associated with substantially higher levels of income.